Progress in Nanofluid Technology: From Conventional to Green Nanofluids for Biomedical, Heat Transfer, and Machining Applications - Beatriz D. Cardoso; Andrews Souza; Glauco Nobrega; Inês S. Afonso; Lucas B. Neves; Carlos Faria; João Ribeiro; Rui A. Lima (Nanomaterials, 2025)
Nanofluids (NFs), consisting of nanoparticles (NPs) suspended in base fluids, have attracted growing interest due to their superior physicochemical properties and multifunctional potential. In this review, conventional and green NF technology aspects, including synthesis routes, formulation, and applications, are discussed. Conventional NFs, involving NPs synthesized using physical and chemical approaches, have improved NP morphology control but are likely to cause environmental and safety concerns. In contrast, green NFs that are plant extract, microorganism, and biogenic waste-based represent a sustainable and biocompatible alternative. The effect of key parameters (e.g., NP size, shape, concentration, dispersion stability, and base fluid properties) on the performance of NFs is critically examined. The review also covers potential applications: in biomedical engineering (e.g., drug delivery, imaging, theranostics, and antimicrobial therapies), in heat transfer (e.g., solar collectors, cooling electronics, nuclear reactors), and precision machining (e.g., lubricants and coolants). Comparative insights regarding green versus conventionally prepared NFs are provided concerning their toxicity, environmental impact, scalability, and functional performance across various applications. Overall, this review highlights the new promise of both green and conventional NFs and provides key opportunities and challenges to guide future developments in this field.